The Relationship Between Sleep Disturbance and Disease Activity in Pediatric Patients With Inflammatory Bowel Disease. Issue 2 (February 2019) - Jarasvaraparn, Chaowapong; Zlomke, Kimberly; Vann, Noelle C.; Wang, Bin; Crissinger, Karen D.; Gremse, David A.
ABSTRACT: Objective: The aim of this prospective cross sectional study was to assess the prevalence of sleep disturbance in children with inflammatory bowel disease (IBD), including the relationships between sleep, inflammatory markers, and disease activity of pediatric patients with IBD. Methods: Pediatric patients with IBD and parents were enrolled in the study. Patients completed the Pittsburgh Sleep Quality Index (PSQI), the Pediatric Daytime Sleepiness Scale, and the Adolescent Sleep Wake Scale (ASWS) surveys. Parents completed the Child Sleep Habits Questionnaire (CSHQ). Disease activity for Crohn disease (CD) was determined by the Pediatric Crohn Disease Activity Index and the Pediatric Ulcerative Colitis Activity Index was used to define disease activity in ulcerative colitis (UC)/indeterminate colitis patients. Results: Fifty-three pediatric patients with IBD (38 CD, 12 UC, and 3 indeterminate colitis) participated in the study. The significant correlations between the CSHQ and Pediatric Crohn Disease Activity Index ( P = 0.002) and the PSQI and Pediatric Ulcerative Colitis Activity Index ( P = 0.04) were found. Youth with UC and indeterminate colitis significantly reported more sleep disturbance than patients with CD, ( P = 0.03, 0.05, and 0.04; PSQI, Pediatric Daytime Sleepiness Scale, ASWS, respectively). Patients self-reported significantly more sleep disturbance than was observed by parents ( P < 0.0001). This study showed the significant correlations between CSHQ score compared to erythrocyte sedimentation rate and albumin ( P = 0.001 and 0.03, respectively). Conclusions: Results suggest that increased disease activity is associated with adverse effects on sleep quality. Based on the results of this study, pediatric patients with IBD should be screened for sleep disturbance. Abstract : Supplemental Digital Content is available in the text